Ties that bind - Bostwick, Marie (Bostwick, Marie. Cobbled Court novel, 2012)
When tragedy threatens to tear her family apart, Margot Matthews discovers that her friendship with the new female pastor and her quilting sisterhood are the only things holding her together as she tries to piece back together her life.